Asuhan Keperawatan Pada Ny. S Dengan Diagnosis Medis Post Operasi Fibroadenoma Mammae (FAM) Sinistra Di Ruang Mawar 2 RSUD dr. Soeselo Kabupaten Tegal - Sholifatul Maulidia; Ahmad Zakiudin; Sukirno Sukirno (STIKes Ibnu Sina Ajibarang, 2023)
Fibroadenoma (FAM) is a small, benign solid lump in the breast consisting of glandular and fibrous tissue. This lump is usually found in young women, often found in teenage girls . Based on data obtained from the Netherlands and America, breast complaints are the main reason for around 3% of women in the world to consult a doctor . Breast cancer is a malignant breast tumor that can become cancer originating from breast tissue (ducts, lobules and other supporting tissue), which differentiates the two, namely shape, consistency, surface, whether it is easy to move or not and the nature of pain .